Extrinsic Apoptosis Pathway Altered by Glycogen Synthase Kinase-3β Inhibitor Influences the Net Drug Effect on NSC-34 Motor Neuron-Like Cell Survival. (10th September 2017) - Kim, Jee-Eun; Lim, Jung Hyun; Jeon, Gye Sun; Shin, Je-Young; Ahn, Suk-Won; Kim, Seung Hyun; Lee, Kwang-Woo; Hong, Yoon-Ho; Sung, Jung-Joon
Abstract : Glycogen synthase kinase-3 β (GSK-3 β ) inhibitors have been suggested as a core regulator of apoptosis and have been investigated as therapeutic agents for neurodegenerative diseases, including amyotrophic lateral sclerosis. However, GSK-3 β has an interesting paradoxical effect of being proapoptotic during mitochondrial-mediated intrinsic apoptosis but antiapoptotic during death receptor-mediated extrinsic apoptosis. We assessed the effect of low to high doses of a GSK-3 β inhibitor on survival and apoptosis of the NSC-34 motor neuron-like cell line after serum withdrawal. Then, we identified changes in extrinsic apoptosis markers, including Fas, Fas ligand, cleaved caspase-8, p38 α, and the Fas-Daxx interaction. The GSK-3 β inhibitor had an antiapoptotic effect at the low dose but was proapoptotic at the high dose. Proapoptotic effect at the high dose can be explained by increased signals in cleaved caspase-8 and the motor neuron-specific p38 α and Fas-Daxx interaction. Our results suggest that GSK-3 β inhibitor dose may determine the summation effect of the intrinsic and extrinsic apoptosis pathways. The extrinsic apoptosis pathway might be another therapeutic target for developing a potential GSK-3 β inhibitor.